Shallow water equations for equatorial tsunami waves. (28th January 2018) - Geyer, Anna; Quirchmayr, Ronald
Abstract : We present derivations of shallow water model equations of Korteweg–de Vries and Boussinesq type for equatorial tsunami waves in the f -plane approximation and discuss their applicability. This article is part of the theme issue 'Nonlinear water waves'.